GLIF: A Declarative Framework for Symbolic Natural Language Understanding - Schäfer, Jan Frederik; Kohlhase, Michael (CEUR Workshop Proceedings, 2020)
With the Grammatical Logical Inference Framework (GLIF), a user can implement the core of symbolic language understanding systems by describing three components, each of which is based on a declarative framework: Parsing (with the Grammatical Framework GF), semantics construction (with MMT), and inference (with ELPI). The logical frameworks underlying these tools are all based on LF, which makes the connection very natural. Example applications are the prototyping of controlled natural languages or experiments with new approaches to natural-language semantics. We use Jupyter notebooks for a unified interface that allows quick development of small ideas as well as testing on example sentences.
CRIS-Team Scopus Importer:2021-04-19